Law Enforcement Against Environmental Pollution by the Way Kanan District Environmental Service - Ati Yuniati; Upik Hamidah; Marlia Eka Putri; Eka Deviani; Sepriyadi Adhan S; Rodhi Agung Saputra (Universitas Kuningan, 2022)
Environmental management and protection is currently a fundamental problem in Indonesia. The form of environmental protection regulation is Law Number 32 of 2009 concerning Environmental Protection and Management. One form of environmental pollution found in Way Kanan Regency is environmental pollution caused by the manufacture of liquid rubber waste. The research method used is a normative-empirical research method, using a statute approach and an in-depth interview approach related to environmental law enforcement against environmental pollution. The problems that will be discussed in this study are How is Law Enforcement by the Environmental Service against environmental pollution in Way Kanan Regency and what are the inhibiting factors for the Environmental Service in implementing environmental pollution law enforcement in Way Kanan Regency.